EFFECTS OF SPENT MUSHROOM SUBSTRATE ON SELECTED PHYSICAL PROPERTIES OF SOIL PLANTED WITH WHITE CABBAGE - Rosa, R.; Franczuk, J.; Rutkowska, A.; Andrejiová, A.; Dydiv, O. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The long-term use of mineral fertilizers in agriculture can have detrimental effects on the natural environment. One potential solution to mitigate these negative impacts is to incorporate natural and organic materials to enrich the soil. A traditional natural fertilizer that has been utilized for centuries around the world, including Poland, is manure. However, systemic changes in Polish agriculture over the past two decades have led to a shortage of this resource. As a result, there is a pressing need to explore alternative sources of organic matter for soil enhancement. One promising option is the use of organic waste materials, such as spent mushroom substrate (SMS). This substrate is a by-product of the cultivation of edible mushrooms, particularly champignons (Agaricus bisporus). Given the scale of mushroom production in Poland, it is estimated that Polish farms generate between 1.6 and 2.0 million tons of this waste, which requires safe disposal and management. Across Europe, the annual production of mushroom substrate exceeds 3 million tons. In a recent experiment, the introduction of spent mushroom substrate provided more organic matter, as well as macro and micronutrients, to the soil compared to farmyard manure (FYM). Measurements taken before the harvesting of cabbage revealed that the physical properties of the soil - namely, topsoil bulk density, porosity, and subsoil moisture - remained consistent between plots treated with SMS and FYM, both of which demonstrated significantly better conditions than the control plot with no organic fertilizer. When plowed in prior to planting cabbage seedlings, both SMS and FYM notably increased the marketable yield of cabbage heads in comparison to the control. The yield-enhancing effects of the two organic fertilizers were found to be quite similar.